(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
The Linear and nonlinear effects in optical fibers are very important and influential factors that effect on the power of the signal transmitted within the optical fiber. In this paper, the mathematical model for these effects was presented. The most important methods used to compensate these losses were also reviewed. The compensation methods reviewed include various linear and nonlinear effects most of the methods reviewed focused on increasing the length of the optical fiber to transmit the signal with the least consumed power and high data transfer rate at low design cost